HELPING RELATIONSHIP ANTARA PERAWAT DENGAN PASIEN DALAM PENYEMBUHAN SKIZOFRENIA DI RUMAH SAKIT JIWA PROF. DR. SOEROJO MAGELANG - Ascharisa Mettasatya Afrilia; Lintang Citra Christiani (Universitas Tidar, 2020)
Abstract: Schizophrenia is one type of mental disorder with the most sufferers after bipolar disorder and depression. It is estimated that 75% of schizophrenics in the age range of 16-25 years are included as age products so that schizophrenics cannot maximize their work and creativity in social life. One effort to improve mental health can be done through therapeutic communication. Helping the relationship as part of therapeutic communication is important to increase patient awareness so that problems that may arise in schizophrenia cases can be handled optimally. This study discusses how to help the relationship between nurses and patients in healing schizophrenia so that it can support the healing of patients. The research method used is a qualitative research method with descriptive analysis techniques. The results showed that nurses are